Accurate absorption spectroscopy of water vapor near 1.64 µm in support of the MEthane Remote LIdar missioN (MERLIN). (September 2019) - Vasilchenko, S.; Tran, H.; Mondelain, D.; Kassi, S.; Campargue, A.
Highlights: The CRDS spectrum of pure and air-broadened water vapor is recorded between 6071.4 and 6080.0 cm −1 . The targeted spectral region is that selected by the MERLIN mission for atmospheric CH4 retrieval. Uncertainty on the interfering water lines may affect the obtained atmospheric methane columns. Line parameters are determined from multi-spectrum fits of spectra recorded at different pressures. The speed dependent Nelkin-Ghatak and Nelkin-Ghatak profile are used to model the line shape and a recommended line list is provided. Abstract: The MERLIN mission (MEthane Remote LIdar missioN) is a space mission dedicated to the methane atmospheric retrieval based on absorption LIDAR measurements at nadir. The methane columns will be obtained by difference between the LIDAR signal at the on-line wavelength corresponding to the R (6) manifold of the 2ν3 band of methane at 6077 cm −1 and the off-line signal at a wavenumber about 1 cm −1 below. As atmospheric water vapor lines may affect the methane retrievals, the present study is dedicated to a detailed laboratory characterization of the interfering water vapor absorption in the targeted region. To this aim, high sensitivity absorption spectra of pure water vapor and water vapor in air are recorded at room temperature using a cavity ring down spectrometer (CRDS) combined with a self-referenced frequency comb. The CRDS recordings cover the 6071.4–6080.0 cm −1 interval with a noise equivalent absorption, α min, on the order of 5 × 10 −11 cm −1 for a 10 −3 cm −1 sampling of the spectra. The measured pure and air-broadened spectra are analyzed using the Nelkin-Ghatak (NG) or the speed-dependent Nelkin-Ghatak (sdNG) profile. A multi-spectrum fitting procedure in which series of spectra recorded at different pressures (between 0.7 and 12 Torr for pure water vapor and between 100 and 700 Torr for H2 O in air) are simultaneously adjusted, is used to retrieve the spectroscopic parameters. Accurate line parameters including self- and air-pressure shifts, self- and air-broadenings, Dicke narrowing and the speed-dependent coefficients are determined for most of the lines with intensity larger than 10 −28 cm/molecule at 296 K. The list is complemented with literature data (in particular from the HITRAN database) to be complete down to a 10 −29 cm/molecule intensity cut-off. The obtained spectroscopic results are discussed in comparison with literature data. Graphical abstract: Image, graphical abstract